The cardiac function characteristics and nursing measures of endoscopic endonasal transsphenoidal approach for growth hormone-secreting pituitary adenoma complicated with cardiomyopathy (内镜下经鼻蝶入路手术治疗生长激素型垂体瘤合并心肌病患者的心功能特征及相关护理要点) - YAN Ying (闫莹); HE Xin (贺欣) (Association of Integrative Nursing, 2023)
Objective To review the cardiac clinical characteristics of patients undergoing endoscopic transsphenoidal approach for the treatment of growth hormone-secreting pituitary adenoma complicated with cardiomyopathy, and summarize the nursing measures to improve nursing quality. Methods The clinical data of 38 cases of patients who underwent endoscopic endonasal transsphenoidal approach for the treatment of growth hormone-secreting pituitary adenoma complicated with cardiomyopathy were collected and analyzed, Using echocardiography to detect the growth hormone(GH) level, left ventricular end-diastolic diameter(LVEDD), septal thickness(ST), left ventricular posterior wall thickness(LVPWT), left ventricular ejection fraction(LVEF) to comparative analysis of cardiac function were made in these patients before surgery and after 3 months. Results GH level, LVIDD, ST, LVPWT and LVEF after resection of pituitary tumor were significantly improved compared with those before resection(P<0. 05). Conclusion Endoscopic transsphenoidal approach for the treatment of growth hormone-secreting pituitary adenoma can significantly improve the cardiac function of patients, and nursing cooperation is conducive to help reduce the incidence of compliaitons and improve the recovery of cardiac function. (目的 回顾性分析生长激素(GH)型垂体瘤患者内镜经蝶入路治疗和护理要点。方法 收集天坛医院神经外科2022年1月-12月内镜经蝶入路治疗GH型垂体瘤合并心肌病患者的临床资料, 总结治疗方法和护理经验, 观察术前及术后3个月GH、左室舒张末压内径(LVEDD)、室间隔厚度(ST)、左室后壁厚度(LVPWT)和左室射血分数(LVEF)变化。结果 本组患者干预后3个月GH、LVEDD、ST、LVPWT平均值较干预前均有明显改善, LVEF较干预前提高。结论 内镜经蝶入路治疗GH型垂体瘤可显著改善患者症状, 配合围手术期针对性护理有助于减轻相关并发症, 改善心功能。)